The potential of DNA methylation markers in the study of obesity - A. F. Nikolaeva; K. O. Petrova; O. V. Vasyukova; R. M. Guseinova; I. R. Minniakhmetov; R. I. Khusainova; N. G. Mokrysheva; V. O. Sigin (Ожирение и метаболизм, 2024)
Obesity is a complex, heterogeneous, actively progressive disease manifested by excessive formation of adipose tissue in the body and usually has a high cardiometabolic risk and specific complications. Currently, new data are emerging that explain the pathogenesis of obesity not only by genetic variations and imbalance between energy intake and expenditure, but also by the influence of epigenetic mechanisms, such as DNA methylation. DNA methylation is the most studied epigenetic modification, whose status in the cell can be altered by various external and internal environmental factors, including diet, lifestyle, and hormones. These changes may lead to dysregulation of genes responsible for metabolic processes associated with the development of obesity. However, studies investigating epigenetic marks as potential mediators of obesity are heterogeneous in design, methodology, and results. This review discusses a conceptual framework analyzing the relationship between DNA methylation, obesity, inflammation, and response to weight loss, including after bariatric surgery, as well as material selection and methodology issues to consider when designing studies in this area.